2020
DOI: 10.3390/catal10091003
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Metals-Doped Nickel Aluminate Spinels for Photocatalytic Degradation of Organic Pollutants

Abstract: Visible-light-activated photocatalysts based on samarium-doped, europium-doped, and gadolinium-doped nickel aluminates (SmNA, EuNA, GdNA) were synthesized. The spinel crystalline structures of the doped mixed metal oxides were demonstrated by X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis. The presence of the rare-earth metals (REMs) was confirmed by the energy-dispersive X-ray (EDX) studies. Ultraviolet-visible-near-infrared (UV-Vis-NIR) spectra revealed that the REMs-doped cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 49 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The modification of NiAl 2 O 4 with GQDs decreased the calcination time, improving the specific surface area of NiAl 2 O 4 compared with the reported data. 35 Finally, the reason for the slight decrease in BET when doping GQDs was that GQDs could not affect the pore diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of NiAl 2 O 4 with GQDs decreased the calcination time, improving the specific surface area of NiAl 2 O 4 compared with the reported data. 35 Finally, the reason for the slight decrease in BET when doping GQDs was that GQDs could not affect the pore diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The points at low relative pressures corresponded to monolayer adsorption and the micropore structure, while the points at high relative pressures were related to multilayer adsorption and the mesopore structure. On the nitrogen adsorption-desorption curves of NiAl 2 O 4 and GQD-NiAl 2 O 4 nanocomposite, the desorption curve resulted in the hysteresis 35 Finally, the reason for the slight decrease in BET when doping GQDs was that GQDs could not affect the pore diameter.…”
Section: Characterizations Of Gqds-nial 2 Omentioning
confidence: 97%
“…Ferrites have also been included in inductors, choke coils, recording heads, and magnetic ampli ers. These properties, together with its high chemical stability and mechanical hardness, make it suitable for electronic industries such as magnetic spin lters, data storage, microwave absorbers, and biomedical areas, where they are very useful for magnetic resonance imaging (MRI), bio-magnetic separation, tumour treatment by hyperthermia, drug delivery and release, catalysis and drug targeting [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [18] used lanthanum chloride (LaCl3) and cerium chloride (CeCl3) to modify graphene oxide (GO), and found that coordination bonds between the rare earth elements and the oxygen-containing groups of GO reduce the surface energy of GO and improve the dispersibility. Regulska et al [19] added rare earth elements to nickel aluminate and found that the addition of rare earth elements refined the original grain size of nickel aluminate. Wu et al [20] added 0.05wt% rare earth elements to Cu-6wt%Fe composites and found that the average grain size was refined from 32 μm to 20 μm.…”
Section: Introductionmentioning
confidence: 99%